Terminus Positions of the Koge Bugt North, Koge Bugt Central and Koge Bugt South Glaciers 2022-2024 ... - Picton, Hannah (NERC EDS UK Polar Data Centre, 2025)
The dataset consists of three shapefiles containing terminus positions of the Koge Bugt North, Koge Bugt Central, and Koge Bugt South glaciers respectively, between 2022-2023. The terminus positions were manually digitised using either Landsat-8 or Landsat-9 imagery, downloaded from the USGS Earth Explorer (https://earthexplorer.usgs.gov/). If suitable optical imagery was unavailable, MEaSUREs Sentinel-1A and Sentinel-1B synthetic aperture radar (SAR) mosaics were employed, downloaded from the National Snow and Ice Data Center (NSIDC; Joughin, 2021). The dataset comprises 71 terminus positions in total, each digitised from imagery collected between 2022-01-11 and 2023-12-08. Hannah Picton acknowledges funding from the E4 DTP (Edinburgh Earth, Ecology and Environment Doctoral Training Partnership), NE/S007407/1. ... : Each terminus position was manually digitised within QGIS using Landsat-8 or Landsat-9 images downloaded from the USGS Earth Explorer (https://earthexplorer.usgs.gov/). If suitable optical imagery was unavailable, MEaSUREs Sentinel-1A and Sentinel-1B synthetic aperture radar (SAR) mosaics were employed, downloaded from the National Snow and Ice Data Center (NSIDC; Joughin, 2021). The details of the specific image from which a given terminus position was digitised is provided in the attribute table of the respective shapefile. These details will also be provided within the supplementary material of the associated publication for this dataset. ...